Preferences For Controlling Occupational Health and Safety Risk In The Building Projects - Ida Ayu Rai Widhiawati (International Journal of Engineering and Emerging Technology, 2021)
Abstract Building projects have the complexity and massive frequency of procurement that can trigger work accidents. Although different efforts have been made, there are still work injuries, one of which is caused by employees who are uncomfortable with the control measures being taken. The aim of this analysis is to find alternatives or solutions in controlling OHS regulation. In order to assess the degree of risk, risk analysis was performed by multiplying the probability value with the concequence. Risk management was performed by referring to the hierarchy of OHS risk control based on OHSAS 18001. Questionnaires were administered using the method of purposeful sampling to assess the choice of field workers and OHS officers for OHS risk management. 168 hazards were described in this study, 24 hazards (14.2%) were classified as low risk, 94 hazards (55.95%) as moderate risk, 49 hazards (29.17%) as high risk, and 1 hazard (0.6%) as very high risk. From the point of view of the OHS officer, the preference for OHS risk control in the very high-risk category was the administrative method, the personal protective equipment (PPE) method in the high-risk category, and the engineering controls were liable for the moderate and low risks. In the meanwhile, from the point of view of the field workers, the control preference in the very high risk category was by administrative method, by the personal protective equipment (PPE) method in the high and moderate risks, and by the engineering controls in the low risk category.